Psychological Stress in People with Dual Sensory Impairment through Usher Syndrome Type II. (May 2015) - Högner, Nadja
Introduction: Due to their dual, sensory impairment, people with Usher syndrome are assumed to have a high risk of stress. The purpose of this study was to assess stress in people with Usher syndrome type II (USH2) and the influence of personal variables such as age, gender, and employment on stress. Methods: Two questionnaires were used: A self-developed questionnaire (SQ) to investigate the frequency and intensity of stress by external stressors within six life domains and the German standardized stress questionnaire Trierer Inventory of Chronic Stress (TICS) to compare frequency of stress between the USH2 sample group and a reference group ( n = 604). The questionnaires were filled in by an ad hoc sample of 262 persons with USH2 (response rate: 93%), mainly recruited from self-help groups (ages 17–79, mean age = 51; 53% female; 32% employed). Differences were determined by using methods of classical test theory. Results: The evaluated SQ shows good indices in terms of item and factor analysis. The greatest stress was seen in the factor "Orientation and Mobility"; in TICS it was in the scale "Chronic Worry." In TICS the USH2 sample showed significantly higher stress on scales that indicate a lack of social-emotional need fulfillment and less stress in those with high expectations ( p = .05). In both questionnaires, stress was dependent on personal variables. Discussion: The results indicate the need for rehabilitation arrangements to reduce stress in people with USH2, especially in the areas of orientation and mobility, chronic worry, and social isolation. In intervention, particular attention should be paid to older, female, and unemployed people. Implications for practitioners: Internal and external resources for people with dual sensory impairment need to be strengthened and systematic programs for learning how to cope with stress need to be established in order to provide clients with successful problem- and emotion-focused coping strategies.